626 What Is the Influence of Negative Pressure Wound Therapy (NPWT) on High-Risk Wounds in Pelvic Oncology?. (19th August 2022) - Al-Aqeel, M; Adlan, A; Stevenson, J
Abstract: Aim: Hindquarter amputation (HQA) has a high incidence of postoperative wound complications. We aim to use the HQA procedure as a model to investigate the potential advantages of negative pressure wound therapy (NPWT) on wound healing complications in high-risk pelvic oncology wounds. Method: We conducted a retrospective analysis of all patients undergoing hindquarter amputation at a single tertiary centre between January 2009 and November 2020. Patients were divided into groups who had and hadn't undergone neoadjuvant radiotherapy (RT) to the pelvic tumour. Results: One hundred six patients were included in the study. 43.4% had NPWT. There was no difference in the incidence of reoperation in the patient group without neo-adjuvant RT between NPWT and conventional dressings (odds ratio [OR], 1.01; p=0.983, 95% confidence interval [CI], 0.365–2.8). However, the use of NPWT decreased the incidence of reoperation among the patients who had NPWT who had received radiotherapy [OR], 0.087; p=0.033, 95% CI, 0.009–0.818). The incidence of wound complications has declined with the increasing use of NPWT between 2009–2020. Conclusions: The application of NPWT reduces the incidence of wound complications in high-risk pelvic oncology wounds. We demonstrated a reduction in the incidence of reoperation due to wound complications in patients who received NPWT following HQA.